St. Anne and her Infant Daugher in Medieval Texts and Images - D-Vasilescu, Elena Ene (Eikón / Imago, 2015)
People are used to thinking of breastfeeding as a rather private biological act. Still, both the New and Old Testaments refer to its spiritual value. Milk nursing and nourishing in general belong not only to the mundane, but also to the divine realm. When St. Anna had the mystical experience through which she knew that she would conceive, she might well have felt instinctively at least some of the above. My paper is concerned with how St. Anna is represented milk-nursing her child in literature in general and in medieval iconography.